Mechanical properties of concrete containing palm oil fuel ash and modified expanded polystyrene beads as replacement materials using finite element method - Ruslan, Mohd Syamil; Osman, Mohamad Hairi; Mahamad, Mimi Suliza; A Rahman, Noor Khazanah; Adnan, Suraya Hani; Salim, Salman; Mat Nor, Ahmad Hakimi (2020)
Nowadays, so much waste material was dumped and produced by the industrial sector. In this research, the Palm Oil Fuel Ash (POFA) and Modified Expanded Polystyrene beads (EPS) were used as replacement material. The purpose of this research was to focus on replacement of the modified expanded polystyrene beads (EPS) as a fine aggregate and the palm oil fuel ash (POFA) as a cement in term of mechanical properties of concrete. For Modified EPS will replace with aggregate from 10.0 % and 20.0 % While, for POFA will replace with cement from 10.0 %, 20.0 % and 30.0 %. The data of the material replacement for POFA and Modified EPS will be taken from previous study. Furthermore, the concrete cubes will be analyzed using software called ABAQUS. ABAQUS software is used because this software can measure the concrete cubes in such detail. This test will be performed on a cube that has reached the age of 28 days by following the previous experimental results. In addition, the software can also validate the work for the stress and strain of the graph by analyzing the concrete cubes. Information on Modified EPS and POFA can be filled in this software. Furthermore, it can also analyze mechanical properties of concrete that containing. Modified EPS and POFA. Indirectly, this will help compare the strength of concrete cube that containing of Modified EPS and POFA.